1987
DOI: 10.1159/000238528
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effect of Ofloxacin on Theophylline Pharmacokinetics in Rats

Abstract: Effect of ofloxacin, a new quinolone antibacterial agent, on the pharmacokinetics of theophylline was studied in rats in comparison with that of enoxacin and cimetidine. Ofloxacin by pretreatment with five oral doses of 50 mg/kg did not increase serum concentrations of theophylline (5 mg/kg, i.v. single) and showed no significant effect on total body clearance, serum half-life (TV,) and AUC of theophylline, while enoxacin by the same pretreatment increased significantly serum theophylline concentrations and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…In the previous study, we have reported that enoxacin pretreatment with five oral doses of 50 mg/kg over a period of 3 days extremely raises serum concentrations of theophylline in rats [3]. Considering the present results, it is conceivable that this elevation of serum theophylline concen trations is induced only by the inhibition of the metabolism of theophylline medi ated by cytochrome P-450-dependent monooxygenase system.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In the previous study, we have reported that enoxacin pretreatment with five oral doses of 50 mg/kg over a period of 3 days extremely raises serum concentrations of theophylline in rats [3]. Considering the present results, it is conceivable that this elevation of serum theophylline concen trations is induced only by the inhibition of the metabolism of theophylline medi ated by cytochrome P-450-dependent monooxygenase system.…”
Section: Discussionsupporting
confidence: 58%
“…Thus, it has been reported that die concurrent administration of enoxacin remarkably raises plasma theophylline concentrations and induces untoward ad verse reactions with theophylline in hu mans [1,2]. With respect to the mechanism of enoxacin interaction with theophylline, the present authors have elucidated re cently that enoxacin extremely raises serum theophylline concentrations and re sults in a significant effect on the theo phylline pharmacokinetics by the inhibi- tion of hepatic microsomal cytochrome-P-450-dependent monooxygenases, the drug-metabolizing enzyme system, in rats [3]. Recently, it has been reported that cimetidine, a typical inhibitor of the drugmetabolizing enzyme system, has the abil ity to induce the enzyme systems by re peated administration, and to modify the effectiveness of concurrent drugs [4,5].…”
Section: Introductionmentioning
confidence: 60%
“…For enoxacin, toxicities apparently related to increased serum theophylline concentrations resulted in cessation of quinolone therapy in 9 of 15 patients (144). Evidence suggested that the mechanism of the drugdrug interaction was interference with demethylation of theophylline by the hepatic P450 enzymes by the 4-oxoquinolone metabolite (189,557,836). Notably, clinically important drug-drug interactions did not occur between theophylline and either norfloxacin (76,348,543,836) or ofloxacin (242,309,543,836).…”
Section: Drug-drug Interactionsmentioning
confidence: 99%
“…However, the in vitro experiments in this study showed that ENX and NFLX inhibited the 7-EC 0-deethyl ase activity in liver microsomes even from the beginning of the reaction; at that time, no metabolite could have been produced from the parent drugs. Okazaki et al (26) have also reported similar results from in vitro experi ments. Recently, Mulder et al (28) inves tigated the effects of ENX, its metabolite oxoenoxacin and OFLX on the oxidative metabolism of theophylline in isolated rat hepatocytes.…”
Section: Discussionmentioning
confidence: 52%
“…Plasma protein binding and renal clearance of theophylline are reported to remain unchanged in patients treated with ENX or OFLX (1,2,5), so that the prolongation of the TI/2 of theophylline is considered to be due to reduced metabolic clearance in the liver. In rats, ENX and OFLX are also reported not to affect serum protein binding (26).…”
Section: Discussionmentioning
confidence: 92%